Distinct maturation, glucose metabolism, and inflammatory function of human monocytes-derived IDECs mediated by anti-IgE and Pam3CSK4 alone or in combination - Gao, Cuie; Zhao, Ying; Ge, Lan; Liu, Wenying; Zhang, Mengjie; Ni, Bing; Song, Zhiqiang (Frontiers in Immunology, 2024)
Background: Cell energy metabolism controls the activation and function of dendritic cells (DCs). Inflammatory dendritic epidermal cells (IDECs) in skin lesion of atopic dermatitis (AD) express highaffinity IgE receptor (FcεRI) and toll-like receptor 2 (TLR2), which mediate the generation and maintenance of inflammation. However, cellular energy metabolism and effector function of IDECs mediated by FcεRI and TLR2 have not been fully elucidated.Methods: IDECs in vitro were treated with TLR2 agonist Pam3CSK4 and anti-IgE alone or in combination for 24 hours. Further, we analyzed the expression of cell surface activation markers, production of inflammatory factors and cellular energy metabolism profiles of IDECs by using flow cytometry, multiplex assay, RNA sequencing, targeted energy metabolism and seahorse assays.Results: Compared to the unstimulated or anti-IgE groups, Pam3CSK4 alone or combined with anti-IgE groups significantly increased the expression of CD80, CD83 and CD86 on IDECs, but did not affect the expression of the above markers in the anti-IgE group. The release of inflammatory cytokines increased in the Pam3CSK4 alone or combined with anti-IgE groups, while a weak increased trend in anti-IgE group. The glycolysis/gluconeogenesis pathway of carbon metabolism was affected in all treatment groups. Furthermore, compared with the control group, we found decrease of pyruvic-acid, up-regulation of PFKM, down-regulation of FBP1, increase of extracellular lactate, glycolysis rate and glycolysis capacity after all treatment, while no difference between each treatment group. However, there was no difference in glycolytic reserve and mitochondrial basic and maximum respiration among all groups.Our results indicate that glycolysis of IDECs may be activated through FcεRI and TLR2 to upregulate inflammatory factors, suggesting that danger signals from bacteria or allergens might evoke inflammatory response of AD disease through glycolysis pathway.